Meningkatkan Pemahaman Siswa Kelas VII-1 SMPN 1 Rao Selatan Terhadap Konsep Beriman Kepada Malaikat Melalui Model Pembelajaran Problem Based Learning - Nurhasrat, Nurhasrat (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve student engagement and learning outcomes on the topic of faith in angels through the implementation of the Problem-Based Learning (PBL) model in Grade VII at SMPN 1 Rao Selatan. This classroom action research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Results from Cycle I indicated an increase in student engagement; however, several challenges remained, such as the dominance of high-achieving students in group discussions and the lack of deep understanding among others. After improvements in Cycle II, the findings showed significant increases in conceptual understanding, critical thinking skills, and group collaboration. This study confirms that the PBL model effectively encourages students to be more active and reflective in learning. However, additional strategies are needed to support students who still struggle with the material.